2016
DOI: 10.1111/mmi.13479
|View full text |Cite
|
Sign up to set email alerts
|

AvaR2, a pseudo γ‐butyrolactone receptor homologue from Streptomyces avermitilis, is a pleiotropic repressor of avermectin and avenolide biosynthesis and cell growth

Abstract: Avermectins produced by Streptomyces avermitilis are effective anthelmintic agents. The autoregulatory signalling molecule that triggers avermectin biosynthesis is a novel butenolide-type molecule, avenolide, rather than common γ-butyrolactones (GBLs). We identified AvaR2, a pseudo GBL receptor homologue, as an important repressor of avermectin and avenolide biosynthesis and cell growth. AvaR2 directly repressed transcription of aveR (the ave cluster-situated activator gene), aco (a key gene for avenolide bios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(73 citation statements)
references
References 54 publications
1
72
0
Order By: Relevance
“…The cell pellet was washed with distilled water, collected by centrifugation and dried to constant weight (Zhu et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The cell pellet was washed with distilled water, collected by centrifugation and dried to constant weight (Zhu et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The finding that σ 8 indirectly represses ave genes suggested that σ 8 initiates transcription of direct repressor(s) of aveR or aveA1 . We recently characterized PhoP (Yang et al, 2015) and AvaR2 (Zhu et al, 2016) as direct repressors of aveR . We also found that SAV742 directly represses transcription of several ave structural genes including aveA1 , but not aveR (Sun et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…The observation that σ 8 has an indirect effect on aveR expression suggests that it regulates aveR through a “cascade” mechanism. However, our search for aveR upstream regulator(s) that mediate the repression of σ 8 on aveR showed that the two known aveR direct repressor genes, phoP (Yang et al, 2015) and avaR2 (Zhu et al, 2016), are not targets of σ 8 . Future studies will identify such direct regulator(s) of aveR and clarify the mechanisms underlying σ 8 function in avermectin production.…”
Section: Discussionmentioning
confidence: 99%
“…Two single mutants of Sputcn32_0304 and Sputcn32_0305, Δ0304 and Δ0305, were constructed. The deletion mutant of Sputcn32_0304 was constructed according to previous studies (39)(40)(41), which can avoid the polar effect on expression of the downstream gene Sputcn32_0303 and facilitate the investigation on its own expression changes. The biofilm biomasses of both single mutants were significantly increased compared to that of the WT strain, and biofilms of both complementation strains C-0304 and C-0305 were restored to the WT level ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All other deletion mutants were constructed according to previous studies (39)(40)(41). To construct the Δ0304 mutant, PCR was used to generate a 1,587-bp DNA fragment upstream (positions Ϫ1443 to 144 relative to the Sputcn32_0304 start codon) and a 1,529-bp DNA fragment downstream (positions 565 to 2094 relative to the Sputcn32_0304 start codon) of the Sputcn32_0304 gene (reserving 144 bp after the start codon for real-time RT-PCR analysis) using primers 0304-5F/0304-5R and 0304-3F/0304-3R, respectively.…”
Section: Methodsmentioning
confidence: 99%